Chinese Muslims in Malaysia - Abdullah @ Chuah Hock Leng, Osman (IIUM Press, 2001)
Chuah, a Malaysian of Chinese origin, converted to Islam in his early 30s and has devoted much of his time since then to promoting Islam and to studying the experiences of other Chinese with similar religious experiences. This book is a result of interviews carried out with other similar converts to discover their experiences. In doing so he gives us a perspective on multicultural Malaysia that is usually ignored by others, but from which there is much to learn. This book now appears to be generally unavailable. 241 pages. Chapters cover topics such as the conceptual and theoretical background to the study, ethnic relations in Malaysia, interactions between Chinese Muslim Converts, non-Muslim Chinese and Muslim Malays, the integration of Chinese Muslims with Malays and the practice of Chinese customs by Chinese Muslim converts.